The Role of Ethical Leadership in Achieving Comprehensive Quality Standards in Public Education Schools in Al-Ardha Governorate (Journal Of Educational and Psychological Researches, 2023)
AbstractThe aim of the research is to identify the role of ethical leadership in achieving comprehensive quality standards in public education schools in the Al-Ardha governorate. To achieve this goal, the descriptive approach was used, the researcher developed a questionnaire consisting of (35) items, divided into two sections: the first one is related to ethical leadership includes (17) items, and the second section relates to total quality management includes (18) items. The research sample consisted of (405) teachers from the stages of public education. The results showed that the level of ethical leadership practice (ethical personal characteristics, ethical administrative features, teamwork, and human relations) recorded high scores. The results also showed there are statistically significant differences in the average degree of moral leadership practice among leaders of general education schools in Al-Ardha governorate according to the variables (years of experience, academic qualification, and the academic stage). There are no differences in the averages and standard deviations of the study sample responses in the level of commitment to the overall quality standards of the leaders of general learning schools in the Al-Ardha governorate due to the two variables (experience and academic qualification). There are statistically significant differences in the mean score of Adherence to the comprehensive quality standards of the leaders of general learning in the Al Ardha governorate according to the variable of the school stage (elementary, intermediate, and secondary). There is a positive correlation relationship with statistical significance at the level of (05) between the average degree of the practice of education school leaders for general learning in Al Ardha governorate for the dimensions of ethical leadership and the average degree of achieving the comprehensive quality standards. The researcher came out with a number of recommendations and suggestions.